The Football Association's Women's Super League and female soccer fans: fan engagement and the importance of supporter clubs. (3rd April 2022) - Leslie-Walker, Anika; Mulvenna, Claire
ABSTRACT: The global soccer market has seen a growth in the professionalization of women's teams and as a result, spectatorship and fandom have augmented. Women's soccer was historically perceived as a taboo; however, stakeholder support has generated visibility and enhanced commercialization opportunities. The Football Association in England instituted the Women's Super League (hereafter WSL) during 2010, and the first season commenced in 2011 with eight teams. Subsequently, in 2021 there were 12 professional women's teams in the top-tier of the league and 11 teams in the championship. A qualitative case study approach is utilized, via the use of semi-structured interviews to explore the demographics and motives of women who watch soccer at the elite level and their socialization into fan communities. The study concludes by acquiring an understanding of the consumption of female soccer fans within the WSL and focuses upon the relationship between supporter clubs and fan socialization.